2006
DOI: 10.1007/s11207-006-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Force-Free Modeling of Coronal Magnetic Fields Part I: A Quantitative Comparison of Methods

Abstract: We compare six algorithms for the computation of nonlinear force-free (NLFF) magnetic fields (including optimization, magnetofrictional, Grad-Rubin based, and Green's function-based methods) by evaluating their performance in blind tests on analytical force-free-field models for which boundary conditions are specified either for the entire surface area of a cubic volume or for an extended lower boundary only. Figures of merit are used to compare the input vector field to the resulting model fields. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
412
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(431 citation statements)
references
References 37 publications
17
412
2
Order By: Relevance
“…Therefore BIE would be slow when extrapolating NLFFF from boundary data with computing grids compatible with current observations. DBIE is expected to make an improvement (Schrijver et al, 2006;Wiegelmann, 2008). Hence we will adopt a suitable parallel computing technique for DBIE.…”
Section: Gpu Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Therefore BIE would be slow when extrapolating NLFFF from boundary data with computing grids compatible with current observations. DBIE is expected to make an improvement (Schrijver et al, 2006;Wiegelmann, 2008). Hence we will adopt a suitable parallel computing technique for DBIE.…”
Section: Gpu Techniquementioning
confidence: 99%
“…As no iteration was performed to determine the set of factors by the BIE method in the comparison against the analytical force-free-field models of Low and Lou (1990). It was expected that completion of the iteration by DBIE will greatly reduce the computation time and should be feasible (Schrijver et al, 2006). Here we just adopt the Case II in Schrijver et al (2006), i.e., only bottom boundary data are used because this type of the boundary condition is close to the case of the Sun.…”
Section: Gpu Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, several different numerical NLFFF extrapolation methods have been developed to calculate the 3-D coronal magnetic fields from the photospheric vector magnetic field measurements. Descriptions, comparisons, and reviews of these methods can be found in the papers by Schrijver et al [2006], Metcalf et al [2008], Schrijver et al [2008], DeRosa et al [2009], Régnier [2007], and Wiegelmann [2008] and in section 5.3 of the book by Aschwanden [2005, and references therein].…”
Section: Introductionmentioning
confidence: 99%